Community case management and unplanned hospital admissions in patients with heart failure: A systematic review and qualitative evidence synthesis. (6th April 2018) - King, Anna Jyoti Louise; Johnson, Rachel; Cramer, Helen; Purdy, Sarah; Huntley, Alyson Louise
Abstract: Aims: The aim of this study was to describe case management as experienced by patients with heart failure and their health professionals with the aim of understanding why case management might contribute in reducing hospital admissions. Background: Heart failure is a common cause of unplanned hospital admission. The evidence for case management in patients with heart failure for reducing admissions is promising. Design: Systematic review and qualitative evidence synthesis. Data source: Searches were conducted in Medline, Psychinfo, Kings Fund database and Cinahl from inception of each database to 16 February 2017. Review methods: Robust systematic review methodology was used to identify qualitative studies describing the experiences of patients with heart failure and healthcare providers of case management. Data were synthesized thematically, and analytic themes were developed. Findings: Five studies (six papers) from which nine descriptive themes were used to determine three analytic themes. This synthesis showed that case management provides positive quality of care for patients, increases perceived access to services and creates more time to ask questions and develop trusted relationships. For health professionals, case management enhanced care by improved relationships with both patients and colleagues although concerns remained around resources, training and inter‐professional conflict. Conclusions: This synthesis emphasizes the importance of the quality of being cared for as a patient and caring as a health professional. Case management enhances communication between patients and health professionals, supports patient self‐care and self‐management and can be an important contributing factor in reducing unplanned admissions for patients with heart failure.